Corporate Governance's Role In Combating Earnings Manipulation: Leveraging Cyber Laws, Forensic Accounting, And Emerging Technologies For Prevention And Early Detection - Nguyen, Trinh Huu (Jurnal Cita Hukum, 2025)
This paper aims to examine the impact of Corporate Governance on Earnings Manipulation, with Cyber Laws, Forensic Accounting Practices, and Emerging Technologies serving as moderating factors. This study, utilizing data from 400 high-tech industry professionals in China, validates the overall research hypothesis through PLS-SEM, demonstrating that strict governance procedures effectively mitigate earnings manipulation. Cyber laws and emerging technologies enhance financial regulation by augmenting oversight and reducing the potential for manipulation, while forensic accounting provides supplementary techniques for fraud detection and compliance. The study advocates for the integration of regulatory and compliance mechanisms, technology, and forensic processes into organizational compliance systems to improve accountability and transparency in financial reporting. Thus, the policy options may include strengthening cybersecurity regulations, advancing technological capabilities, and incorporating forensic accounting into the organizational management framework.